Pelatihan Berbahasa Inggris ‘English For Business’ untuk Mahasiswa Keguruan - Siti Asiyah; Ardhana Januar Mahardhani; Laela Rosidha (Gapenas Publisher, 2022)
The ability to speak English is a mandatory thing for all students, including students from the teacher study program. In addition, students from the teacher training study program are also required to know about business, this is to answer market needs and the development of increasingly strong globalization currents. The existence of the necessity of cooperating with foreign partners as absorbers of graduates must also be taken into account. The service activity aims to answer the challenges so that teaching students are able to compete in the business world. The activity was carried out on March 1-2, 2022 and was carried out at the University of Muhammadiyah Ponorogo. Training starts from coordination of activities, implementation of activities, and evaluation and follow-up of activities